2017
DOI: 10.1002/ejic.201601530
|View full text |Cite
|
Sign up to set email alerts
|

Palladium(II) Complexes of Ambidentate and Potentially Cyclometalating 5‐Aryl‐3‐(2′‐pyridyl)‐1,2,4‐triazine Ligands

Abstract: The 5-aryl-3-(2′-pyridiyl)-1,2,4-triazine ligands under study L 1 ; 5-(3-methoxyphenyl)-(PyTZ3Me-OPh) L 2 ; 5-(4-methoxyphenyl)-(PyTZ4MeOPh) L 3 ; 5-(4-trifluoromethylphenyl)-(PyTZ4CF 3 Ph) L 4 ; 5-(4-fluorophenyl)-(PyTZ4FPh) L 5 ; and tris-3,5,6-(2′-pyridyl)-1,2,4-triazine (Py 3 TZ) L 6 ] react with [(COD)PdCl 2 ] (COD = 1,5-cyclooctadiene) to form complexes [(L 1-6 )PdCl 2 ] with N,N bidentate binding ligands, also including the potentially N,N,N tridentate ligand L 6 . This was concluded from an in-depth N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 101 publications
(252 reference statements)
1
9
0
Order By: Relevance
“…Similar behaviour is observed for the protoligands HCNN at potentials lying about 0.7 V lower than those corresponding to the complexes (Figures S6 to S17, Tables S2 and S3). Consistent with reports of similar complexes, [8,9,13,43–46,48–53,57–63] we thus assume that the lowest unoccupied molecular orbital (LUMO) is centred largely on the pyridine‐thiazole/‐benzothiazole moiety.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…Similar behaviour is observed for the protoligands HCNN at potentials lying about 0.7 V lower than those corresponding to the complexes (Figures S6 to S17, Tables S2 and S3). Consistent with reports of similar complexes, [8,9,13,43–46,48–53,57–63] we thus assume that the lowest unoccupied molecular orbital (LUMO) is centred largely on the pyridine‐thiazole/‐benzothiazole moiety.…”
Section: Resultssupporting
confidence: 85%
“…Electrochemical experiments were carried out on the series of Pd(II) complexes to assess the impact of the variation of the three groups in the C ^N^N ligands. Previous studies showed a good correlation between electrochemical data with absorption energies [2,4,12,13,31,38,40,43,[45][46][47][48][57][58][59][60][61][62][63] and DFT-calculated frontier orbitals and energies have been benchmarked with electrochemical data. [13,23,33,[45][46][47]63] At a first glance, all Pd(II) complexes showed a first reversible one-electron reduction wave at around À 1.7 V for the thiazole complexes and at À 1.6 V for the benzothiazole derivatives (Figure 1, Table 1).…”
Section: Electrochemistry and Dft-calculated Frontier Orbitalsmentioning
confidence: 99%
See 2 more Smart Citations
“…6-Phenyl-2,2′-bipyridine (Hphbpy, 3 ) was selected as the C^N^N-chelating ligand and directly synthesized from 2,2′-bipyridine (bpy, 1 ) and phenyl lithium 2 in moderate yield but on a scale of 0.5 g (Scheme ). The reaction of Hphbpy 3 with [PdCl 2 (cod)] 4 (cod = 1,5-cyclooctadiene) at reflux for 18 h resulted in smooth metalation of the phenyl ring without the need for an external base. , However, an attempt to synthesize the analogous Pt­(II) complex using [PtCl 2 (cod)] failed, and thus, K 2 [PtCl 4 ] 5 was used as the starting material with good success. , The targeted chlorido compounds 6 and 7 were obtained in very good yield and easily converted to azido complexes 8 and 9 by refluxing with sodium azide in a mixture of water and acetone (Scheme ). The azido complexes 8 and 9 were then reacted at room temperature in a catalyst-free iClick reaction with a slight excess of electron-poor alkynes 4,4,4-trifluoro-2-butynoic acid ethyl ester (TFBE, 10 ) and dimethyl acetylenedicarboxylate (DMAD, 11 ) and methyl propiolate ( 12 ) to give the triazolato products 13–18 , with complexes 15 and 18 only prepared in a kinetic NMR tube experiment and not isolated.…”
Section: Resultsmentioning
confidence: 99%